Developing Students’ Critical Thinking Through High Order Thinking (HOT) Question In Reading Comprehension - Wawat Srinawati (Jurnal Serambi Ilmu, 2020)
The writers used qualitative research. It is a research studies that investigate the qualitiy of relationship, activities, situations or materials are frequently. In doing this research, the writers took the data using triangulation technique by collecting the data from observation, questionnaire and interview. This technique was used because the writers wanted to examine the data credibility and also avoid the bias data in research. The overall attitude of respondents interest in English and reading is in the category of positive attitudes. The questionnaire were 20 statements and devided into 3 categories, those are interest; perception/critical thinking and HOTS understanding. This classroom observation showed that in skill gathering, evaluating information and ideas students got 60% with teacher’s guide and 40% with students’ initiation This is indicated by the total score of respondents which amounted to 393 and lies between a score of 300 (median) and 400 (quartile 3), which is the score limit in the positive attitude category. Each respondent's attitudes about students' interest in English, reading and text spread in the very positive attitude category 40%, positive attitude 50% and negative attitude 10%.